METHOD OF THE COMPUTER SIGNAL PROCESSING OF THE CHEMICAL CURRENT SOURCE RESPONSE TO A CURRENT PULSE - Dzenzerskij, V. A.; Beda, M. A.; Zhitnik, N. E.; Plaksin, S. V. (Radio Electronics, Computer Science, Control, 2013)
The further development of pulse methods for diagnosis and monitoring of the technical state of chemical power sources is underway, due to their high information content and relative simplicity of implementation. No less important is the possibility of combining the functions of non-stationary charging methods of chemical power sources with methods of impulse control of their condition, which simplifies the implementation of adaptive charging mode that best fits the requirements of operation of chemical power sources. The form of the response signal contains extensive and sufficient objective information about the kinetics of the electrochemical process, which directly affects the parameters of chemical power sources. However, the processing and analysis of the results of measurements manually are very complicated and does not automate the process of monitoring chemical power sources. Objective of this paper is to develop methods for computer processing of the response signal of chemical current source to the pulse of current to automate technical state control the chemical source current in real time. The method of the computer signal processing of the chemical current source response to a current pulse, the base of which is detection of coordinates of points containing information about kinetics of process on the preliminary smoothed out signal-response and determination of the characteristic parameters of the chemical current source is proposed.